2020
DOI: 10.1177/0961203320959702
|View full text |Cite
|
Sign up to set email alerts
|

Biologics targeting type I interferons in SLE: A meta-analysis and systematic review of randomised controlled trials

Abstract: Objective The feed-forward loop of type I interferons (IFNs) production and subsequent immunopathology of systemic lupus erythematosus (SLE) has been hypothesised to be disrupted with inhibition of IFNα or type I IFN receptor subunit 1 (IFNAR). This systematic review and meta-analysis present the treatment efficacy and safety profile of monoclonal antibodies inhibiting IFNα or IFNAR. Methods A search was done using Medline, Embase and ClinicalTrials.gov for biologics targeting IFNα or IFNAR in SLE up to 3 Jan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
(140 reference statements)
0
9
0
3
Order By: Relevance
“…As expected, the use of systemic glucocorticoids (sGC) and immunosuppressants such as cyclophosphamide are also associated with a greater risk of herpes zoster and other viral infections. 24,34,35 Cytomegalovirus D 1 1 2 X Xand upper respiratory tract viral infections are common in the SLE population, and may present with severe and atypical manifestations that mimic SLE flares. 28,36 Respiratory infections are one of the most common causes of hospitalization and early mortality in patients with SLE.…”
Section: Relationship Between Sle and Risk Of Viral Infectionsmentioning
confidence: 99%
“…As expected, the use of systemic glucocorticoids (sGC) and immunosuppressants such as cyclophosphamide are also associated with a greater risk of herpes zoster and other viral infections. 24,34,35 Cytomegalovirus D 1 1 2 X Xand upper respiratory tract viral infections are common in the SLE population, and may present with severe and atypical manifestations that mimic SLE flares. 28,36 Respiratory infections are one of the most common causes of hospitalization and early mortality in patients with SLE.…”
Section: Relationship Between Sle and Risk Of Viral Infectionsmentioning
confidence: 99%
“…A meta-analysis of randomized controlled trials of mAbs targeting IFNα or type I IFN receptor subunit 1 (IFNAR) has been recently published (35). Three studies including a total of 927 patients showed that anifrolumab 300 mg was more effective than placebo in achieving SRI-4 and BICLA responses.…”
Section: Inhibition Of Ifn Pathwaymentioning
confidence: 99%
“…Основные результаты, касающиеся эффективности и безопасности АФМ при СКВ, суммированы в серии аналитических обзоров [59,60] и метаанализах РПКИ [61][62][63].…”
Section: эффективностьunclassified
“…Данные метаанализа РПКИ MUSE и TULIP, в которые вошли 839 пациентов, получавших АФМ (n=372) и плацебо (n=467) [63], свидетельствуют о более высокой эффективности АФМ по сравнению с плацебо в отношении следующих параметров: эффект по индексу BICLA (отношение шансов (ОШ) -0,44; 95%-й доверительный интервал (ДИ): 0,34-0,59; p<0,00001); снижение ≥50% счета CLASI (ОШ=0,36; 95% ДИ: 0,21-0,60; p=0,0001); эффект по индексу SRI (4) (ОШ=0,52; 95% ДИ: 0,30-0,90; p=0,02). Сходные данные получены в другом метаанализе [61], включавшем 459 пациентов, леченых АФМ, и 468 пациентов, получавших плацебо. Установлено, что лечение АФМ ассоциировалось с увеличением эффективности терапии по индексам SRI (4) (ОШ=1,91; p=0,02), BICLA (ОШ=2,25; p<0,00001), снижением ≥50% по индексу CLASI (ОШ=2,79, p=0,0002 через 12 нед., ОШ=2,61, p=0,004 через 52 нед.)…”
Section: эффективностьunclassified